2011
DOI: 10.1063/1.3643714
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the energetics of the oxygen reduction reaction on the Pd-Co electro-catalysts: Insight from first principles

Abstract: We report here results of our density functional theory based computational studies of the electronic structure of the Pd-Co alloy electrocatalysts and energetics of the oxygen reduction reaction (ORR) on their surfaces. The calculations have been performed for the (111) surfaces of pure Pd, Pd(0.75)Co(0.25) and Pd(0.5)Co(0.5) alloys, as well as of the surface segregated Pd/Pd(0.75)Co(0.25) alloy. We find the hybridization of dPd and dCo electronic states to be the main factor controlling the electrocatalytic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 37 publications
2
79
0
Order By: Relevance
“…In the CO 2 reaction pathway, the free energy G for the CO 2 product was calculated as follows [Eq. ]: trueΔG=ΔE+ΔZPE+ΔGu-TΔS …”
Section: Methodsmentioning
confidence: 99%
“…In the CO 2 reaction pathway, the free energy G for the CO 2 product was calculated as follows [Eq. ]: trueΔG=ΔE+ΔZPE+ΔGu-TΔS …”
Section: Methodsmentioning
confidence: 99%
“…Manogaran and Hwang 45 studied the role of the surface-subsurface interlayer interaction in enhancing the oxygen hydrogenation towards water in Pd 3 Co alloy catalysts. Their work clarified that the subsurface Co atoms facilitate the ORR by lowering the activation barriers for O/OH hydrogenation; however, the Co atoms lying below the subsurface far from the surface layer have no significant involvement in the modification of the surface reactivity towards O hydrogenation.Experimental and theoretical works confirmed that the Pd-skin alloy catalysts are the key systems for improving the ORR activity 26,35,36,[39][40][41][42][43][44][45][46][47][48][49]. Many works have been performed to clarify the ORR activity versus the Co content for PdCo films and carbonsupport PdCo nanoparticles where Co atoms can be at the topmost surface layer [25][26][27][28][29][30][31][32].…”
mentioning
confidence: 95%
“…Many works have been performed to clarify the ORR activity versus the Co content for PdCo films and carbonsupport PdCo nanoparticles where Co atoms can be at the topmost surface layer [25][26][27][28][29][30][31][32]. Despite the fact that the Pd-skin/PdCo electrocatalysts are very stable and active for the ORR,26,35,36,[39][40][41][42][43][44][45][46][47][48][49] no similar works are available in the literature for Pd-skin/PdCo alloy catalysts. Understanding the effects of the Co content on the ORR activity of Pd-…”
mentioning
confidence: 99%
“…Both the decreased O and OH adsorption energies on PtTi are beneficial for the reduction of O and OH intermediates to water as well as alleviating the surface poisoning from these species, thus generating the modified oxygen reaction kinetics [55]. The downshifts of the deband center of Pt relative to the Fermi level means the decrease of an electron backdonation from the Pt 5d orbital to the 2p* orbital of O and OH [54,56,57], consequently weakening the OePt and OHePt bonding. This is considered to be the possible origination for the higher ORR activities and catalytic durability of HNPePt 75 Ti 25 alloy than Pt/C and NPePt catalysts.…”
Section: Resultsmentioning
confidence: 97%